Material Sputtering with a Multi-Ion Species Plasma Focused Ion Beam - Valerie Brogden; Cameron Johnson; Chad Rue; Jeremy Graham; Kurt Langworthy; Stephen Golledge; Ben McMorran (Advances in Materials Science and Engineering)
Focused ion beams are an essential tool for cross-sectional material analysis at the microscale, preparing TEM samples, and much more. New plasma ion sources allow for higher beam currents and options to use unconventional ion species, resulting in increased versatility over a broader range of substrate materials. In this paper, we present the results of a four-material study from five different ion species at varying beam energies. This, of course, is a small sampling of the enormous variety of potential specimen and ion species combinations. We show that milling rates and texturing artifacts are quite varied. Therefore, there is a need for a systematic exploration of how different ion species mill different materials. There is so much to be done that it should be a community effort. Here, we present a publicly available automation script used to both measure sputter rates and characterize texturing artifacts as well as a collaborative database to which anyone may contribute. We also put forth some ideas for new applications of focused ion beams with novel ion species.